Cancers Attributable to Overweight and Obesity From 2012 to 2014 in Nigeria: A Population-Based Cancer Registry Study - Odutola, Michael K.; Olukomogbon, Temitope; Igbinoba, Festus; Otu, Theresa I.; Ezeome, Emmanuel; Hassan, Ramatu; Jedy-Agba, Elima; Adebamowo, Sally N. (Frontiers in Oncology, 2019)
Background: Overweight and obesity are known risk factors for chronic diseases including cancers. In this study, we evaluated the age standardized incidence rates (ASR) and proportion of cancers attributable to overweight and obesity in Nigeria. Methods: We obtained incidence data from the databases of two population-based cancer registries (PBCRs) in Nigeria (Abuja and Enugu cancer registries), on cancer site for which there is established evidence of an association with overweight or obesity based on the International Agency for Research on Cancer and the World Cancer Research Fund classification. We analyzed the data using population attributable fraction (PAF) for overweight or obesity associated cancers calculated using prevalence data and relative risk estimates in previous studies. Results: The two PBCRs reported 4,336 new cancer cases (ASR 113.9 per 100,000) from 2012 to 2014. Some 21% of these cancers were associated with overweight and obesity. The ASR for overweight and obesity associated cancers was 24.5 per 100,000; 40.7 per 100,000 in women and 8.2 per 100,000 in men. Overall, only 1.4% of incident cancers were attributable to overweight and obesity. The ASR of cancers attributable to overweight and obesity was 2.0 per 100,000. Postmenopausal breast cancer was the most common cancer attributable to overweight and obesity (n=25; ASR 1.2 per 100,000). Conclusion: Our results suggest that a small proportion of incident cancer cases in Nigeria are potentially preventable by maintaining normal body weight. The burden of cancer attributed to overweight and obesity is still relatively small in Nigeria, but it is likely to increase in future.